The White Man’s Burden and U.S. Past and Present Imperialism: From Civilizing Mission to Democracy Promotion The Cases of the Philippines (1898-1946) and Afghanistan (2001-2014) - Maskri, Sara; Boussahoua, Meriem; Mihoubi,Ahmed (University of Ammar Theledji -Laghouat, 2020)
This study aims to explore the imprint of Kipling's "The White Man's Burden " on U.S. past and present imperialism. It therefore aims to investigate the "new" U.S. imperialism of the twenty-first century and its linkage to U.S. imperialism of the late nineteenth and early twentieth centuries. Moreover, this work aims to examine how the white man's "burden” turned from civilizing mission to democracy promotion, and to demonstrate how the U.S. imperialism in the Philippines and Afghanistan is covered by civilizing mission and democracy promotion. To achieve those aims, the study compares the case of the Philippines (1898-1946) to the case of Afghanistan (2001-2014) and investigated how the two cases have various similarities and revealed the U.S.‘s true intentions. Lastly, the study finds that both U.S. past and present actions reflect the sentiments carried in Kipling’s poem. Besides, it also discovers that U.S. imperialism in the late nineteenth and early twentieth centuries has a number of similarities to U.S. imperialism in the early twenty-first century. Finally, the study finds that the white man’s “burden” turned from spreading civilization to promoting democracy and that the United States uses these moral missions to veil its imperial behavior.